The Role of Immigrants, Asylum Seekers, and Refugees in Confronting Maine’s Demographic Challenges - Glover, Robert (Maine Policy Review, 2016)
The state of Maine currently faces a looming “demographic winter.” The state and its communities will struggle to maintain viable and vibrant communities in the decades to come due the current demographic situation, and will encounter a host of economic and political challenges as a result. Working to make Maine an attractive destination for immigrants, asylum seekers, and refugees must be at the forefront of efforts to address this challenge. This article lays out the difficult demographic situation that Maine currently faces and will face in the years to come and articulates why, more than ever, fostering greater diversity in the state’s population is essential to its future.